2007
DOI: 10.1103/physrevb.75.035103
|View full text |Cite
|
Sign up to set email alerts
|

Cohesion ofBaReH9andBaMnH9

Abstract: Density functional calculations are used to calculate the structural and electronic properties of BaReH9 and to analyze the bonding in this compound. The high coordination in BaReH9 is due to bonding between Re 5d states and states of d-like symmetry formed from combinations of H s orbitals in the H9 cage. This explains the structure of the material, its short bond lengths and other physical properties, such as the high band gap. We compare with results for hypothetical BaMnH9, which we find to have similar bo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 28 publications
(27 reference statements)
1
12
0
Order By: Relevance
“…These states strongly hybridize with the T spd states to form the σ -bonds, which is evident from the H1 s and T spd characters of both the valence and conduction bands. These results are consistent with a previous electronic structure calculation by Singh et al 29. for BaReH 9 , which contains the hydride complex ReH 9 .…”
Section: Resultssupporting
confidence: 93%
“…These states strongly hybridize with the T spd states to form the σ -bonds, which is evident from the H1 s and T spd characters of both the valence and conduction bands. These results are consistent with a previous electronic structure calculation by Singh et al 29. for BaReH 9 , which contains the hydride complex ReH 9 .…”
Section: Resultssupporting
confidence: 93%
“…[20][21] The hydrogen density in BaReH 9 (134 g/L) is approximately twice that of liquid hydrogen at ambient pressure, indicating that hydrogen atom is chemically precompressed. [20][21][22][23][24] Markopoulous et al 23 examined theoretically the high pressure behavior of BaReH 9 and predicted that metallization occurs at 115 GPa assuming the crystal structure of BaReH 9 remains in the ambient pressure structure.…”
Section: Introductionmentioning
confidence: 99%
“…As the most hydrogen-rich stoichiometric metal salt, BaReH 9 crystallizes with ionic bonding between Ba 2+ and ReH 9 2– in the hexagonal NiAs-type structure with respect to the Ba and Re positions (space group P 6 3 / mmc, Z = 2; Figure ). , The hydrogen density in BaReH 9 (134 g/L) is approximately twice that of liquid hydrogen at ambient pressure, indicating that the hydrogen atoms are chemically precompressed. Markopoulos et al examined theoretically the high-pressure behavior of BaReH 9 and predicted that metallization occurs at 115 GPa, assuming that the crystal structure of BaReH 9 remains in the ambient-pressure structure.…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by the discovery of K 2 ReH 9 , other types of cations have been used to extend the [ReH 9 ] 2– family, including Na 2 ReH 9 , NaKReH 9 , ((C 2 H 5 ) 4 N) 2 ReH 9 , and BaReH 9 . , For elements of group VII, K 2 TcH 9 is the only known technetium compound incorporating similar nine-coordinate [TcH 9 ] 2– units . No analogous manganese compound has yet been reported, while theoretical studies have suggested its viability. , Among the above-mentioned compounds, BaReH 9 has the highest (4.5:1) hydrogen to metal ratio. Unfortunately, because of the high atomic weight of the metal atoms, the hydrogen content is only 2.7 wt %, too small for use as a hydrogen storage material …”
Section: Introductionmentioning
confidence: 99%